The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijerph18179024
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Diabetes Mellitus and Tooth Extraction Due to Periodontal Disease and Dental Caries in the Japanese Population

Abstract: Diabetes mellitus is closely related to oral health. We aimed to determine the relationship between diabetes mellitus and tooth extraction due to periodontal disease and dental caries. Japan’s second nationwide survey data collected from 4 June to 10 June 2018 was used to identify reasons for tooth extraction among patients aged > 40 years. General dentists collected information on patients who underwent tooth extraction procedures, and the presence of diabetes mellitus was determined through interviews. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Participants who answered "yes" were identified as self-reported diabetics, and the others were not self-reported diabetics. [9][10][11] Participants with fasting blood glucose ≥126 mg/dL (7.0 mmol/L) or glycosylated hemoglobin ≥6.5% were considered to be bio-assayed diabetics. Both self-reported and bio-assayed diabetics were considered to be diabetics.…”
Section: Variables and Definitionsmentioning
confidence: 99%
“…Participants who answered "yes" were identified as self-reported diabetics, and the others were not self-reported diabetics. [9][10][11] Participants with fasting blood glucose ≥126 mg/dL (7.0 mmol/L) or glycosylated hemoglobin ≥6.5% were considered to be bio-assayed diabetics. Both self-reported and bio-assayed diabetics were considered to be diabetics.…”
Section: Variables and Definitionsmentioning
confidence: 99%
“…Factors associated with the use of dental services in diabetic people (Andrea Petricia Ramirez Ortega) 529 with diabetes mellitus are dental caries, gingivitis, and periodontitis [11], [12]. Several studies have identified the relationship between diabetes and periodontal diseases by observing advanced periodontitis in patients with type 2 diabetes mellitus (DM2) and high levels of glycosylated hemoglobin (HbA1c) [13]- [15].…”
Section: Introductionmentioning
confidence: 99%
“… 7 In clinical settings, T2DM and periodontal diseases have a positive correlation. 8 , 9 Patients with more severe diabetes tend to have more serious periodontal diseases and vice versa. Therefore, the histopathological examination of periodontal tissue changes is very significant in the early diagnosis of periodontal diseases induced by diabetes.…”
Section: Introductionmentioning
confidence: 99%